1992
DOI: 10.1139/f92-187
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Heavy Metals on Benthic Communities at the Clinch River (Virginia): Evaluation of an Index of Community Sensitivity

Abstract: Benthic communities (sampled once annually from 1986 to 1989) at stations impacted by copper and zinc were characterized by reduced species richness, reduced abundance, and a shift in community composition from sensitive to tolerant taxa. Benthic community structure varied annually due to fluctuations in stream discharge and improvements in water quality. Sensitivity of 13 dominant taxa to Cu was measured in outdoor experimental streams by exposing organisms to Cu (25 μg/L) for 10 d. Sensitivities (si), define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 10 publications
5
65
2
Order By: Relevance
“…These two species were found only in one station (12 th ) associated with aquatic plants, like found in other study (Brodersen et al, 2001). Tanytarsini has correspondingly been reported as sensitive taxa (Clements and Cherry, 1988;Clements et al, 1992). In the present study, only Tanytarsini species was found at sampling site 12.…”
Section: Disscussion Chironomidae Species Communitysupporting
confidence: 81%
“…These two species were found only in one station (12 th ) associated with aquatic plants, like found in other study (Brodersen et al, 2001). Tanytarsini has correspondingly been reported as sensitive taxa (Clements and Cherry, 1988;Clements et al, 1992). In the present study, only Tanytarsini species was found at sampling site 12.…”
Section: Disscussion Chironomidae Species Communitysupporting
confidence: 81%
“…In preference experiments we found that small amounts of contaminants that do not cause physiological effects may interfere with the behaviour and thereby alter predator-prey and competitive interactions between species (Peterson et al, 2011). Contaminants, especially heavy metals, can change the outcome of competitive interactions (Clements et al, 1992;Landis et al, 1997;Pratt et al, 1997). Our results clearly show that the adverse effects of contaminants on feeding behaviour are greater on the endemic amphibian than on the exotic fish species.…”
Section: Discussionmentioning
confidence: 60%
“…Reductions in mayfly taxa (Clements et al 2000), shifts in community dominance from intolerant taxa to Chironomidae (Winner et al 1980), and community changes such as reduction in species richness or abundance (Clements et al 1992, Schultheis et al 1997) have been reported. Studies have looked at impacts from multiple heavy metals (Clements and Rees 1997), as well as specific contaminants such as copper (Leland, et al 1989).…”
Section: Introductionmentioning
confidence: 99%